2022
DOI: 10.1371/journal.pone.0273041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the persistence of post COVID-19 symptoms on critical patients requiring invasive mechanical ventilation and non-critical patients

Abstract: Background During follow-up, patients severely affected by coronavirus disease 2019 (COVID-19) requiring invasive mechanical ventilation (IMV), show symptoms of Post-Intensive Care Syndrome (PICS) such as cognitive impairment, psychological disability, and neuromuscular deconditioning. In COVID-19 pandemic, it is a priority to develop multidisciplinary post-acute care services to address the long-term multisystemic impact of COVID-19. Research question Which are the most relevant multisystemic sequelae in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Some authors even report complete patient recovery one year after the acute phase, even in those patients with worse respiratory mechanics during invasive MV ( 117 ). However, other studies have shown that 60 to 70% of neuropsychiatric symptoms persisted between 3 and 6 months in patients who received MV ( 118 , 119 ). The emergence of psychiatric symptoms, including psychological distress, anxiety, depression, sleep disorders, and alterations, has been documented in survivors of severe illnesses ( 120 ), including those recuperated from severe infections with other coronaviruses ( 121 , 122 ).…”
Section: Pathophysiology Of Long Covidmentioning
confidence: 87%
See 1 more Smart Citation
“…Some authors even report complete patient recovery one year after the acute phase, even in those patients with worse respiratory mechanics during invasive MV ( 117 ). However, other studies have shown that 60 to 70% of neuropsychiatric symptoms persisted between 3 and 6 months in patients who received MV ( 118 , 119 ). The emergence of psychiatric symptoms, including psychological distress, anxiety, depression, sleep disorders, and alterations, has been documented in survivors of severe illnesses ( 120 ), including those recuperated from severe infections with other coronaviruses ( 121 , 122 ).…”
Section: Pathophysiology Of Long Covidmentioning
confidence: 87%
“…A study of 81,337 volunteers showed a significant association between symptomatic COVID-19 and reduced cognitive function, especially in cases involving MV ( 141 ). MV alone, even without COVID-19, can cause neurological complications, which may contribute to long COVID neurological manifestations ( 119 , 177 ). Even fully recovered individuals displayed poorer cognitive performance than uninfected counterparts, indicating a link between symptomatic COVID-19 and cognitive impairment ( 141 ).…”
Section: Pathophysiology Of Long Covidmentioning
confidence: 99%
“…Patients requiring ICU admission and treatment with invasive mechanical ventilation have been shown to exhibit symptoms of post-intensive care syndrome (PICS) during follow-up, which includes cognitive impairment, neuromuscular deconditioning, and psychological disability. Some authors have suggested that COVID-19 critical patients undergoing prolonged mechanical ventilation, sedative use, and steroid treatment may be more susceptible to developing PICS ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The largest was a population-based study involving 456,002 individuals from the United Kingdom at least 4 weeks after COVID-19, where arthralgia was present in 2% to 3% of the patients [72]. In 10 other studies, including 9756 patients overall, a prevalence of joint pain ranging from 10% to 19% was described [35,38,40,41,45,46,51,58,69,73], while 11 studies assessing post-COVID-19 symptoms in 28,303 patients showed higher figures, between 20% and 29% [28,34,42,43,47,49,64,66,71,75,76]. Most of these patients were contributed by Wang et al [71].…”
Section: Joint Pain In Post-covid-19 Patientsmentioning
confidence: 99%